Pelatihan Pembuatan Website E-Commerce dengan Woocommerce Guna Menumbuhkan Semangat Technopreneurship pada HMIF - Asrul Abdullah; Gusti Ardhasna Fauzan; Rizky Wahyu Prasetyo (IKIP PGRI Bojonegoro, 2021)
The high competition in the world of work makes graduates demanded not only capable of hard skills but also capable of soft skills. The development of soft skills for students can be trained by participating in extracurricular activities such as UKM (student activity unit), or student associations. One of the soft skills that has become a priority in this community service is an entrepreneurial spirit supported by adequate hard skills. Efforts are made by training in e-commerce website creation with WooCommerce. The method of mentoring provided in this community service starts from the discourse method, namely providing concepts / theories from Wordpress and WooCommerce, the question and answers (QnA) method, namely by giving participants the opportunity to ask questions about technical and non-technical matters of the system, simulation method / direct practice on a web browser that has been installed with WordPress and Woocommerce including adding products, adding discounts, managing orders and viewing sales. The result of this dedication is that the level of participants' knowledge increased from the pre and post test results from 40,001% to 71,668%. In addition, the level of interest and enthusiasm of the participants to immediately apply what has been obtained was 85.75%.. Tingginya persaingan di dunia kerja membuat para lulusan dituntut tidak hanya mampu pada hard skill tetapi juga mampu dalam soft skill. Penanaman soft skill kepada mahasiswa dapat diasah dengan mengikuti kegiatan ekstrakurikuler seperti UKM (unit kegiatan mahasiswa), atau himpunan mahasiswa. Salah satu soft skill yang menjadi prioritas dalam pengabdian ini adalah jiwa wirausaha yang didukung dengan kemampuan hard skill yang memadai. Upaya yang dilakukan adalah dengan pelatihan pembuatan website e-commerce dengan WooCommerce. Metode pendampingan yang diberikan dalam pengabdian ini dimulai dari metode ceramah yakni memberikan konsep / teori dari Wordpress dan WooCommerce, metode question and answers (QnA) yakni dengan memberikan peserta kesempatan bertanya akan hal-hal teknis dan non teknis dari sistem yang dijelaskan, metode simulasi / praktik langsung di web browser yang sudah di-install wordpress dan woocommerce termasuk penambahan produk, menambahkan diskon, mengelola order dan melihat penjualan. Hasil dari pengabdian ini adalah tingkat pengetahuan peserta meningkat dari hasil pre dan post test dari 40,001% ke 71,668%. Selain itu, tingkat ketertarikan dan semangat peserta untuk segera mengaplikasikan apa yang telah diperoleh sebesar 85,75.